CHARACTERIZATION AND CULTURAL VALUES OF THE MAIN CHARACTERS OF THE FILM â€œLEAP YEARâ€ BY ANAND TUCKER - Virtianti, Rika; Yuliasari, Ria (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2021)
The research aims to describe the cultural values ​​contained in the film Leap Year and to describe the characterizations of the two main characters of the film. The research method used is descriptive qualitative to analyze the elements of cultural values ​​and characterizations in this film. Analysis of cultural elements was carried out using the Koentjaraningrat theory, while characterization analysis was carried out using the Tasrif theory. Observations show that this film displays many cultural values ​​in the form of belief systems, social systems, economic and livelihood systems, language and communication systems, as well as art systems, but there is no cultural element in the form of knowledge systems and technology systems. The observations also show that the characterization is carried out by the concept of physical descriptions, depiction of the way of thinking and awareness, reactions to an event, direct analysis from the author and other people's conversations about the characters, but there is no depiction of characterizations through environmental discussions.